Effectiveness of Cognitive Restructuring on Rumination in Girls with Self-Harm - Masoumeh Alimirzaee; Mahmood Borjali; Nader Monirpoor (Iranian Journal of Educational Research)
Objective: The purpose of this study was to investigate the effectiveness of cognitive restructuring training on the rumination of adolescent girls suffering from self-harm. Methods: The semi-experimental research method was pre-test-post-test and follow-up with a control group. The statistical population of this research was all female students suffering from self-injury, age range 15-18 years old in Baharestan schools in 2023. The number of 54 people who had self-harm in the last 6 months and had visited the counseling clinics were selected, and they were randomly assigned to the experimental and control groups by accessible sampling method. The research tools included the rumination scale (Nolen-Hoeksma and Maro, 1991) and ISAS self-injury test. The subjects of the experimental group underwent eight 90-minute sessions of cognitive restructuring training, and the control group did not receive any intervention, and a follow-up was done after one month. Multivariate covariance analysis was used to analyze the data. Results: After examining the assumptions of multivariate covariance analysis, the test results showed that there is a significant difference between rumination of two groups (p<0.01), also the effect size shows that group membership accounts for 36.4% of the changes in ego-centered rumination explains 39.5% of symptom-oriented rumination changes and 29.9% of antecedent/consequence-oriented rumination changes. Conclusions: According to these findings, it can be concluded that cognitive rehabilitation is effective and has reduced the rumination of girls suffering from self-injury.